2000
DOI: 10.1108/eum0000000007253
|View full text |Cite
|
Sign up to set email alerts
|

Building a case for evidence: research at the International Records Management Trust, Rights and Records Institute

Abstract: The availability of documentary evidence strengthens civil society by helping to protect legal rights and prevent human rights violations. Legal redress, voting rights, land registration and pension claims all depend upon the availability of records. Conversely, the loss of control of records undermines the state's ability to protect the people. Furthermore, in the absence of well-managed records, information can be manipulated, transparency becomes impossible and fraud flourishes. Citizens cannot participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Despite the production of graduates by the University of Namibia with Diplomas and Degrees in records and archives management, the study established that records management in the Public Service of Namibia was carried out by unskilled and untrained personnel. The study findings confirm earlier studies by Barata et al (2001); Nengomasha (2009) and Nengomasha and Beukes-Amiss (2002). Records keeping staff were supervised by staff (Chief Control Officers) from the general administration cadre “General Services” with no records management background.…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the production of graduates by the University of Namibia with Diplomas and Degrees in records and archives management, the study established that records management in the Public Service of Namibia was carried out by unskilled and untrained personnel. The study findings confirm earlier studies by Barata et al (2001); Nengomasha (2009) and Nengomasha and Beukes-Amiss (2002). Records keeping staff were supervised by staff (Chief Control Officers) from the general administration cadre “General Services” with no records management background.…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Taylor’s observations are confirmed by several surveys of records in Ministries and Departments (Barata et al , 2001; Namibia Resource Consultants (NRC), 2002; Nengomasha, 2004; Nengomasha and Beukes-Amiss, 2002). Several studies on records management in Namibia (Abankwah and Hamutumwa, 2017; Barata et al , 2001; Keakopa, 2007; Nengomasha, 2009; Nengomasha and Beukes-Amiss, 2002; Nengomasha and Nyanga, 2012) have highlighted records challenges which include failure to develop and implement records classification schemes; appraisal and development of records retention schedules; and congestion in offices due to non-appraisal and disposal of records. Missing records and records and loss of records in poor storage conditions through fire and water have also been reported (Nengomasha and Nyanga, 2012).…”
Section: Records Management Challenges In Namibiamentioning
confidence: 63%
“…Scholars such as Abioye ( 2014), Barata et al (2000), Loussouarn (2006), Lowry (2012), Mnjama (2009a, 2009b), Mukembo (2000), Poyser and Milne (2011), RMJ 25,3 Saurombe (2014), Valtonen (2007) have written about the role of records management in the provision of justice. Indeed, in many ways, records and justice are inseparable concepts.…”
Section: The Contribution Of Records To Provision Of Justicementioning
confidence: 99%
“…Records represent a major source of information and are almost the only reliable and legally verifiable data source that can serve as evidence of decisions, actions and transactions in the public service, as opposed to oral evidence (Barata et al, 2000;Wamukoya, 2000). This is also emphasised by Force (2013, p. 25) when indicating that Lord Chief Baron Gilbert suggested that written records are more trustworthy than oral evidence.…”
Section: The Contribution Of Records To Provision Of Justicementioning
confidence: 99%
See 1 more Smart Citation